Dry Eye Disease in Physically Active Individuals: The Role of Environmental Factors – A Narrative Review - Mordal, Natalia; Ściebura, Kacper; Walendziak, Weronika; Zienkiewicz, Damian; Makulec, Gabriela; Domosud, Karolina; Wiśniewska, Wiktoria; Ostaszewska, Magdalena; Majchrzyk, Milena; Malczyk, Anna (Quality in Sport, 2026)
Background. Dry eye disease (DED) is a multifactorial disorder of the ocular surface characterized by tear film instability, hyperosmolarity, inflammation, and neurosensory abnormalities. Environmental stressors and systemic factors play a significant role in its development. Physically active individuals are likely to be exposed to such conditions. Aim. To summarize current evidence on the impact of environmental factors and hydration on the development and severity of dry eye disease, with emphasis on physically active populations. Materials and methods. A narrative review was conducted using literature indexed in PubMed and Google Scholar databases, including studies published between 2001 and 2024. The publications were selected based on their relevance to epidemiology and pathophysiology. Results. DED affects a substantial proportion of the population worldwide. Environmental factors such as low humidity, air pollution, temperature variations, ultraviolet radiation and dehydration contribute to ocular surface stress. These factors influence tear osmolarity and may exacerbate symptoms, particularly in physically active individuals exposed to increased environmental and physiological stress. Conclusions. Environmental exposure and hydration status are important contributors to dry eye disease. Physically active individuals may be at increased risk due to combined exposure to environmental conditions and fluid imbalance, highlighting the importance of preventive strategies in this population.